A Study of Bonds Market in Malaysia - SOONG, SING YING; MANSUR, SYAHIRA (Enhanced Knowledge in Sciences and Technology, 2022)
The study is conducted to figure out the most influential variable in Malaysia’s conventional bonds and Sukuk pricing and determine the factors that affect the most influential variable. The variables tested are the components found in the formula of calculating bond price, including yield to maturity, period to maturity, and coupon rate. The data used are collected from Bond Info Hub and divided into four groups, which are government conventional bonds, corporates conventional bonds, government Sukuk, and corporates Sukuk. The most influential variable is determined from the results of multiple linear regression analysis while the factors that affect the most influential variable.is determined by using the secondary research method. According to the findings of this study, the most influential variable in the pricing of conventional bonds issued by the government, Sukuk issued by both government and corporates is coupon rate whereas the most influential variable in conventional corporates bonds pricing is yield to maturity. Besides, the factors that affect coupon rate are prevailing interest rate and the issuer’s creditworthiness while the yield to maturity may be affected by the prevailing interest rate, coupon rate, and inflation rate.